Maulid Nabi dalam Kajian Astronomi Modern - Kamilan, Ikhsan; rasyidin, rasyidin (University of Muhammadiyah Sumatera Utara, 2022)
The results of this paper (this study) state that what is considered by the majority of Muslims so far is in accordance with the facts. The 9th of the early Rabbi is a date that is in accordance with the facts with indications that can be held, that is by putting 30 days because it is not possible to see the new moon at that time. The majority of Muslims consider that the Prophet Muhammad was born on Monday in the month of Rabiul beginning in 671 m there are a lot of lies in the present, this is about determining the date, month and month of the birth of the Prophet. So this article tells about boundaries and contains the selection of the strongest opinions regarding differences of opinion using the method and explanation of our philosophy (astrology) using the library research method with a historical approach (historical). And the 9th of the early Rabbis is Monday as calculated in the words of the Prophet Muhammad, the differences that occurred regarding the birth of the Prophet caused by several factors that are speculative. One of them is nasiah which is an Arabic custom.